2015
DOI: 10.1209/0295-5075/111/18007
|View full text |Cite
|
Sign up to set email alerts
|

Cascading failures of interdependent modular scale-free networks with different coupling preferences

Abstract: As one of the most important mesoscopic properties of networks, the community structure plays an important role in cascading failures on isolated networks. However, the study for understanding the influences of the community structure on the cascading failures on interdependent scale-free networks remains missing. In this paper, we investigate cascading failures on interdependent modular scale-free networks under inner attacks and hub attacks from the global and local perspective. We mainly analyse the inter-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Shao et al [ 46 ] applied a study on the clustering of two fully coupled networks and applied it to partially interdependent networks with clustering. Tian et al [ 22 ] investigated cascading failures in interdependent modular scale-free networks under inner attacks and hub attacks from the global and local perspectives. They found that the assortative coupling in communities (ACIC) is more beneficial in resisting cascading failures than random coupling in communities (RCIC) and assortative coupling with communities (ACWC).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Shao et al [ 46 ] applied a study on the clustering of two fully coupled networks and applied it to partially interdependent networks with clustering. Tian et al [ 22 ] investigated cascading failures in interdependent modular scale-free networks under inner attacks and hub attacks from the global and local perspectives. They found that the assortative coupling in communities (ACIC) is more beneficial in resisting cascading failures than random coupling in communities (RCIC) and assortative coupling with communities (ACWC).…”
Section: Related Workmentioning
confidence: 99%
“…From the perspective of functional properties, the load of nodes was taken into account when the authors established different models to study the cascading failure of interdependent networks in recent research literatures [ 18 , 19 , 20 , 21 ]. Many works have adopted degree [ 22 , 23 ], betweenness [ 24 , 25 , 26 , 27 ], or degree of degree [ 28 ] as the initial load of nodes. In addition, was used as the initial load of an edge , where represents the coupled strength between two coupled nodes i and m , and is the degree of node i [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important factor that affects the robustness of interdependent networks is the property of dependency links, including coupling preference [18][19][20], directionality, and dependency strength. Coupling preference determines the way that dependency links are established between subnetworks, such as assortative coupling, disassortative coupling, and random coupling based on node degree or betweenness [21].…”
Section: Introductionmentioning
confidence: 99%